Instructional leadership in the transformation of deep learning: a case study of data-driven strategies in an Indonesian primary school - Irma Pangestika; Karsono Karsono; Akhmad Arif Musadad (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
This study aims to analyse how a primary school principal exercises instructional leadership to translate the Deep Learning policy into practice through data-driven decision making and a peer-tutoring strategy. The study uses a qualitative single-case design at SDN 8 Boyolali, Central Java, a school appointed as a target site of the BBGTK (Centre for Teacher and Education Personnel Development) Deep Learning programme. Data were collected through in-depth interviews with the principal, six teachers, the school operator, and the supervising school inspector; classroom observations of four classes; and document analysis of the school’s Education Report Card (Rapor Pendidikan) and budget documents. Data were analysed using the interactive model of Miles, Huberman, and Saldaña, and triangulated across sources and techniques. The findings reveal four interrelated leadership practices: (1) reframing Deep Learning as joyful, meaningful, and lasting learning; (2) data-driven prioritisation of programmes based on the Education Report Card; (3) cross-generational peer tutoring that pairs the school operator and younger teachers with senior teachers to bridge the digital gap; and (4) two-way reflective coaching after classroom observation. The novelty of this study lies in articulating an integrative instructional leadership model that combines Education Report Card analysis as the operational entry point for principal decision-making, the deployment of the school operator and younger teachers as legitimate cross-generational peer tutors, and the use of an internal learning community (Wolu Maju) as the dissemination forum for external training a configuration not previously documented in Indonesian primary-school research. Theoretically, the study extends instructional leadership theory by showing that data-driven leadership can operate effectively in resource-constrained primary schools without expensive technology, and that distributed leadership can extend beyond the teacher cadre to include non-teaching personnel. Empirical evidence of impact includes mean classroom-observation scores of 4.2–4.5 on a five-point 6C rubric in classes led by teachers who completed the BERDIKARI training (compared with 3.2–3.8 in transition classes), the institutionalisation of an IDR 7,500,000 digital-literacy programme in the 2025 School Activity and Budget Plan (RKAS), and the sustained operation of the Wolu Majulearning community across 18 sessions over twelve months.